Identification of Flies Found at The Mojoarum Landfill - Dharmawati, Asti Gusni (LPPM Universitas Muhammadiyah Riau, 2024)
Landfills often become a source of complex environmental problems, especially in urban areas. Poorly managed waste not only poses aesthetic issues but also creates breeding grounds for various organisms that can potentially cause health problems for humans. This study aimed to identify fly species found in a landfill using fresh shrimp bait and to evaluate the effectiveness of the bait in attracting various fly species. The research was conducted at four bait placement points in the landfill area of Mojoarum, Surabaya. Observations were made at 07.00-09.00 and 15.00-17.00. Fresh shrimp bait was used to capture flies, which were then reared and identified based on their morphological characteristics. The results revealed four fly species: Chrysomya megacephala (331 individuals), Musca domestica (74 individuals), Fannia sp. (21 individuals), and Sarcophaga haemorhoidalis (6 individuals). C. megacephala was the most dominant species, indicating that the landfill provides ideal conditions for this species. M. domestica was also found in significant numbers, demonstrating its adaptability to the landfill environment. The fresh shrimp bait proved effective in attracting C. megacephala and M. domestica, but less effective for Fannia sp. and S. haemorhoidalis. These findings provide important insights into the composition of fly species in landfills and their implications for waste management and environmental health. Improved waste management is necessary to reduce the health risks posed by flies, particularly those species that can act as disease vectors.